Pengaruh Rob Terhadap Perubahan Pendapatan Petani Tambak di Kecamatan Tirto Kabupaten Pekalongan - Febrian, Ramadhan; Eva, Banowati; Hariyanto, Hariyanto (Geo-Image, 2019)
This study aims: To find out the tidal flood conditions by using a Geographic Information System. (2) Knowing the effect of tidal floods on population income. (3) Knowing adaptation strategies for rob floods. This study uses descriptive quantitative research methods with simple linear regression statistical analysis techniques. The results showed that the results showed that all villages in the northern part of the Tirto sub-district were affected by the tidal floods. The results of linear regression analysis between tidal flood heights and farmer farmer income showed a correlation value (R) of 0.32 and a coefficient of determination (R2) of 0.10 which means that both variables have a low relationship and influence. The adaptation strategy of the farmer to the tidal flood is that the community makes improvements to the pond land by means of waring, making retaining embankments and planting mangroves. The suggestion from this research is that the parameters used to determine the tidal flood area should be more complete. In addition, the development of similar studies to determine the effect of tidal flood heights with farmer farmer income must consider the ownership factors, the location of the ponds of each farmer and the productivity of the farm.